Crohn’s Disease, Ulcerative Colitis, and Rheumatoid Arthritis: The Relationship Between Gut Microbiota and the Development of Autoimmune Diseases - González-Vásquez, Juan Carlos (2025)
The gut microbiota is fundamental for immune and homeostatic regulation of various systems. Its imbalance has been associated with autoimmune diseases, which underscores the need to thoroughly investigate its impact on the etiology and systemic complications of these conditions. This study describes how intestinal dysbiosis is a crucial factor in the development or evolution of inflammatory diseases such as Crohn’s disease, ulcerative colitis, and rheumatoid arthritis, mainly through its ability to modulate immune responses, and highlights promising therapeutic strategies. The modulation of gut microbiota offers not only therapeutic potential but also preventive approaches to minimize the occurrence of autoimmune diseases.